Respuesta :

Answer:

Part (a)

Given quadratic: [tex]y=x^2+2x-8[/tex]

Factored form

To factor, find two numbers that multiply to -8 and sum to 2: 4 and -2

Rewrite the middle term of the quadratic as the sum of these number:

[tex]\implies y=x^2+4x-2x-8[/tex]

Factorize the first two terms and the last two terms separately:

[tex]\implies y=x(x+4)-2(x+4)[/tex]

Factor out the common term [tex](x+4)[/tex]:

[tex]\implies y=(x-2)(x+4)[/tex]

Zeros

The zeros of the quadratic polynomial are the x-coordinates of the points where the graph intersects the x-axis, i.e. when y = 0

[tex]\implies y=0[/tex]

[tex]\implies (x-2)(x+4)=0[/tex]

[tex]\implies (x-2)=0\implies x=2[/tex]

[tex]\implies (x+4)=0\implies x=-4[/tex]

Therefore, the zeros are 2 and -4

Vertex

The x-coordinate of the vertex is the midpoint of the zeros.

[tex]\textsf{midpoint}=\dfrac{-4+2}{2}=-1[/tex]

To find the y-coordinate of the vertex, substitute the found value of x into the given equation:

[tex]y=(-1)^2+2(-1)-8=-9[/tex]

Therefore, the vertex is (1, -9)

------------------------------------------------------------------------------------------------

Part (b)

Given quadratic:  [tex]y=-x^2-9x-14[/tex]

Factored form

To factor, first factor out -1:

[tex]y=-(x^2+9x+14)[/tex]

Now find two numbers that multiply to 14 and sum to 9: 7 and 2

Rewrite the middle term of the quadratic as the sum of these number:

[tex]y=-(x^2+2x+7x+14)[/tex]

Factorize the first two terms and the last two terms separately:

[tex]y=-(x(x+2)+7(x+2))[/tex]

Factor out the common term [tex](x+2)[/tex]:

[tex]y=-(x+7)(x+2)[/tex]

Zeros

The zeros of the quadratic polynomial are the x-coordinates of the points where the graph intersects the x-axis, i.e. when y = 0

[tex]\implies y=0[/tex]

[tex]\implies -(x+7)(x+2)=0[/tex]

[tex]\implies -(x+7)=0 \implies x=-7[/tex]

[tex]\implies (x+2)=0 \implies x=-2[/tex]

Therefore, the zeros are -7 and -2

Vertex

The x-coordinate of the vertex is the midpoint of the zeros.

[tex]\textsf{midpoint}=\dfrac{-7+(-2)}{2}=-4.5[/tex]

To find the y-coordinate of the vertex, substitute the found value of x into the given equation:

[tex]y=-(-4.5)^2-9(-4.5)-14=6.25[/tex]

Therefore, the vertex is (-4.5, 6.25)

Ver imagen semsee45
Ver imagen semsee45
ACCESS MORE